Novel Drugs for Hypertension and Heart Failure: Struggling for a Place Under the Sun - Faselis, Charles; Boutari, Chrysoula; Doumas, Michael; Imprialos, Konstantinos; Stavropoulos, Konstantinos; Kokkinos, Peter (Current Pharmaceutical Design, 2017)
Backgound: Current drug therapy for the management of arterial hypertension and heart failure has provided substantial benefits but has also some limitations. LCZ696, a dual inhibitor of angiotensin receptor blockers and neprilysin, and finerenone, a non-steroidal mineralocorticoid receptor antagonist, are two recently developed novel agents for the management of these conditions. Methods: This review aims to present the pathophysiological basis for the use of these two novel drugs, critically discuss available clinical data, and provide future perspectives. Results: LCZ696 seems a very promising antihypertensive agent, that additionally generates clinically meaningful benefits in patients with heart failure with reduced injection fraction and raises expectations for the management of patients with heart failure with preserved ejection fraction. Finerenone aims to be safer than current aldosterone antagonists and has been so far tested in patients with heart failure and in patients with albuminuria. First available data are very promising for the efficacy of the drug, while it provides a better safety profile than current mineralocorticoid antagonists. Conclusion: LCZ696 and finerenone are two novel drugs for the management of arterial hypertension and heart failure. First available data point toward important clinical benefits from their use. Future large trials further investigating the cardiovascular profile of these agents will establish the use of these drugs.
Keywords: hypertension